Role of the RNA binding protein IGF2BP1 in cancer multidrug resistance - Gola, Aldana Magalí; Bucci-Muñoz, María; Rigalli, Juan Pablo; Ceballos, María Paula; Ruiz, María Laura (Biochemical pharmacology, 2024)
The insulin-like growth factor-2 mRNA-binding protein 1 (IGF2BP1), a member of a conserved family of single-stranded RNA-binding proteins (IGF2BP1-3), is expressed in a broad range of fetal tissues, placenta and more than sixteen cancer types but only in a limited number of normal adult tissues. IGF2BP1is required for the transport from nucleus to cytoplasm of certain mRNAs that play essential roles in embryogenesis, carcinogenesis, and multidrug resistance (MDR), by affecting their stability, translation, or localization. The purpose of this review is to gather and present information on MDR mechanisms in cancer and the significance of IGF2BP1 in this context. Within this review, we will provide an overview of IGF2BP1, including its tissue distribution, expression, molecular targets in the context of tumorigenesis and its inhibitors. Our main focus will be on elucidating the interplay between IGF2BP1 and MDR, particularly with regard to chemoresistance mediated by ABC transporters.